Evidence of Negative Effects of Defect Size and Older Patient Age by Quantitative CT-Based 3D Image Analysis in Ultraporous Beta-Tricalcium Phosphate Grafted Extremity Bone Defects at One Year - Timothy A. Damron; Kenneth A. Mann (Advances in Orthopedics)
Introduction. Synthetic bone graft materials are commonly used to fill defects after curettage of benign bone lesions. Ultraporous beta tricalcium phosphate (TCP) is a popular synthetic compound used in this situation. Prior clinical studies based on plain X-ray analysis suggest incorporation of TCP is incomplete, even when combined with bone marrow (BMA). Purpose. The purpose was to analyze volumetric CT-based changes in defects grafted with TCP with/without BMA in a completed prospective RCT to objectively determine (1) relationship between size and age versus TCP incorporation and (2) whether there is an advantage to addition of BMA. Methods. Twenty-one patients with CT scans at ≥1 year follow-up available for digital analysis (TCP=10, TCP w/BMA =11) form the study population. CT image stacks were evaluated by creating volumetric masks using MIMICS imaging software for total defect, graft remaining, and graft incorporated volumes graft incorporation endpoints. Results. Overall, there was significant (p=0.0029) negative correlation (r2 = 0.38) between defect size and ratio of incorporated bone to defect size. This relationship remained strong (r2 = 0.56) particularly for defects > 20 cc but not for smaller defects. Bone width was also a significantly related factor (r2 = 0.94), with less graft incorporation in larger bone sites, in part likely due to the linear relationship between defect size and bone width. Relationship with age was complex and closely tied to defect volume. For larger defect volumes, younger patients were more successful at graft incorporation. Although age itself was not an independently significant factor, as defect volume increased, advanced age more negatively impacted new bone formation. Conclusions. Larger size defect and affected bone and advancing age appear to be important negative factors in synthetic graft incorporation. Results showed no advantage to addition of BMA to TCP.